Phytomass yield, nutrients accumulation and biological nitrogen fixation by single and associated green manures - Perin, Adriano; Santos, Ricardo Henrique Silva; Urquiaga, Segundo; Guerra, José Guilherme Marinho; Cecon, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the effects of sole and intercropping systems of the summer green manures sunnhemp (Crotalaria juncea) and millet (Pennisetum americanum) in phytomass yield, content and accumulation of nutrients and biological nitrogen fixation (BNF). The experimental design was a randomized complete block with four replicates, and treatments consisted of green manures sunnhemp, millet, sunnhemp + millet and spontaneous vegetation. The sunnhemp stood out in the phytomass yield, being 108% greater than the spontaneous vegetation and 31% superior to millet. In the sunnhemp + millet intercropping, the leguminous contributed with 65% of the total dry matter. The presence of sunnhemp resulted in larger contents of N and Ca, while millet and the spontaneous vegetation showed larger content of potassium. The accumulation of P and Mg was strongly influenced by the phytomass yield, reaching high values in the presence of sunnhemp, while the accumulation of N and Ca was a result of the largest contents as well as the largest phytomass yield in the treatments with the leguminous. The BNF was 61% in the intercropping and 57% in sole cropping, incorporating to soil via BNF 89 and 173 kg/ha of N, respectively, being an excellent strategy for increasing soil nitrogen.